Characterizing breast conditions at an open-access breast clinic in South Africa: a model that is more than cancer care for a resource-limited setting. Issue 1 (December 2017) - Rayne, Sarah; Lince-Deroche, Naomi; Hendrickson, Cheryl; Shearer, Kate; Moyo, Faith; Michelow, Pam; Rubin, Grace; Benn, Carol; Firnhaber, Cynthia
Abstract Background While most breast-related research focuses on cancer, presentation of symptomatic persons in non-screened environments requires understanding the spectrum of breast diseases so as to plan services in resource-constrained settings. This study presents the variety of breast disease managed at a government, open-access breast clinic in South Africa. Methods We performed a retrospective file review using a systematic random sample of patients 18 years and above presenting for breast care over a 14-month period. We collected demographics, clinical characteristics, management and final diagnoses from the first visit and twelve subsequent months. Results The final sample contained 365 individuals (97 · 5% women). Most were black, unmarried and South African citizens with a median age of 43 years (IQR 31–55) . Of those reporting their status (24 · 1%) 38 · 6% were HIV-positive. A mass (57 · 0%) and/or pain (28 · 5%) were the most common symptoms. Imaging and breast biopsies were required in 78 and 25% of individuals, respectively. Nearly half of biopsies identified breast cancer (44 · 1% of women ≤40 and 57 · 3% for women >40). Benign conditions (47 · 7%) and no abnormality (18 · 2%) were common final classifications among women. There was no difference between the final classifications of patients who self-referred versus those who were formally referred from another health care provider. Nearly half of the participants (46 · 6%) travelled 20 km or more to attend the clinic. Conclusions Benign breast conditions far outweighed cancer diagnoses. As breast cancer awareness increases in resource-limited countries, facilities offering breast care require administrative and clinical preparation to manage a range of non-cancer related conditions.